A sodium ion battery soft and hard carbon negative electrode active material and its preparation method and application
By combining carbonized reed straw with asphaltene to form a core-shell structure, and adding pore-forming agents and sodium replenishing agents, the problem of a negative electrode material that needs to carry sodium ions is solved for sodium-ion batteries, achieving high specific capacity and low first-cycle loss rate. effect.
Patent Information
- Application Number
- CN202410780528.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-17
AI Technical Summary
Sodium ion batteries need to find a negative electrode material that can carry sodium ions, because the ion radius of sodium ions is greater than the ion radius of lithium ions, resulting in the original graphite layer structure being inapplicable.
Carbonized reed straw is used as hard carbon, which is wrapped by asphaltene soft carbon to form a core-shell structure. In the presence of pore-forming agent and sodium supplementing agent, the negative active material has a higher specific surface area and more active sites. .
It achieves high specific capacity and low first-cycle loss rate of sodium-ion batteries, and improves the cycle efficiency and mechanical strength of the battery.
Smart Images

Figure CN118367130B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a sodium ion battery soft and hard carbon negative electrode active material, and a preparation method and application thereof. Background Art
[0002] Lithium ions have the advantages of high energy density, green environmental protection, ultra-long cycle life, excellent energy conversion efficiency, high-rate charge-discharge process, and no obvious memory effect.
[0003] However, China's lithium reserves are very small, only 80 million tons. With the rapid development of electric vehicles and large-scale energy storage, it is estimated that the global lithium reserves will not be able to meet the demand for electric vehicles by 2036 at the latest. Therefore, it is difficult to support the rapid development of both electric vehicles and large-scale energy storage industries by relying solely on lithium-ion batteries. However, sodium ions have shown great potential in applications in related fields due to their convenient sources, abundant natural reserves, non-toxicity and chemical stability. The development of a low-cost, high-safety alternative lithium battery technology has become an urgent need. As an emerging battery technology, sodium-ion batteries have gradually entered people's field of vision with their unique advantages and potential.
[0004] The high energy density and low cost of sodium batteries make them a suitable candidate for large-scale energy storage. This is crucial for the sustainable development of energy systems. With higher energy density and lower cost, sodium batteries can replace lithium-ion batteries, reduce dependence on rare and expensive materials, and reduce energy costs. Research on sodium batteries has promoted progress in fields such as materials science, electrochemistry, and engineering. By studying sodium batteries, scientists can better understand basic processes such as ion transport and chemical reactions, and develop new high-performance materials and technologies. Sodium-ion batteries have advantages over lithium-ion batteries in terms of safety, operating temperature, and cycle period. In addition, the over-discharge characteristics of sodium-ion batteries also make them potentially useful in battery transportation.
[0005] However, for sodium-ion batteries to replace lithium-ion batteries, it is not possible to simply replace lithium ions with sodium ions. Since the ionic radius of sodium ions (1.02 Å) is larger than that of lithium ions (0.76 Å), the graphite layer structure that can carry lithium ions is not suitable for sodium ions. Therefore, if you want to develop sodium-ion batteries, you must find a negative electrode material that can carry sodium ions.
[0006] Currently, there are two types of hard carbon materials and soft carbon materials used as negative electrodes for sodium-ion batteries, including biomass materials, carbon-based materials, metal oxides, and alloy materials. Hard carbon refers to carbon materials that cannot form graphite when carbonized at >2500°C. The interior of hard carbon is a cross-linked network of disordered regions and graphite regions, so it has a rigid structure at high temperatures. Due to the disordered and curved graphene layers, sodium ions can be embedded between carbon layers, adsorbed on the graphene surface, and gathered in the nanopores formed by graphene stacking.
[0007] Asphalt is mainly divided into petroleum asphalt and coal tar asphalt due to its different sources and production processes. It has a high carbon atom ratio and is rich in small-sized aromatic molecular compounds. It is composed of aromatic nuclei and side chains. It is easy to form nearly parallel stacked carbon layers during heating, and is an ideal carbon precursor for preparing carbon negative electrodes. Among them, petroleum asphalt is a by-product of heavy oil processing, containing a mixture of hydrocarbons and non-hydrocarbons, mainly composed of carbon, hydrogen, oxygen, sulfur and other elements. Petroleum asphalt is the residue after crude oil distillation. Its main use is as infrastructure material, raw material and fuel. It is currently characterized by overcapacity, low price, difficulty in processing, environmental pollution and serious waste.
[0008] Asphaltene materials are soft carbon materials with poor sodium storage capacity, low active sites, and slow reaction kinetics. They need to be regulated to meet the requirements of battery use. Summary of the invention
[0009] In view of this, the purpose of the present invention is to provide a soft and hard carbon negative electrode active material for a sodium ion battery and a preparation method and application thereof. The negative electrode active material has a large specific surface area and many active sites. The assembled sodium ion battery has the advantages of large specific capacity and low first-cycle loss rate.
[0010] The present invention provides a sodium ion battery soft and hard carbon composite negative electrode active material. The preparation raw materials include asphaltene, carbonized reed straw, a pore former and a sodium supplementer in a mass ratio of (30-50): (15-30): (10-20): (10-25).
[0011] Preferably, the carbonized reed straw is prepared according to the following method:
[0012] In a N2 atmosphere, the reed straw was heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300 min, then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30 min, and cooled to obtain carbonized straw.
[0013] Preferably, the pore-forming agent is melamine;
[0014] The sodium supplement is sodium hydrogen phthalate.
[0015] The present invention provides a method for preparing the soft and hard carbon composite negative electrode active material for a sodium ion battery according to the above technical solution, comprising the following steps:
[0016] The carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent are mixed, solvent toluene is added, stirred evenly, and freeze-dried to obtain core-shell powder;
[0017] The core-shell powder and the carbonized support are carbonized under an inert atmosphere to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery.
[0018] Preferably, the freeze-drying temperature is -38 to -42°C, the vacuum degree is -0.1 MPa, and the time is 10 to 24 hours.
[0019] Preferably, the core-shell powder and the carbonized support are carbonized under an inert atmosphere comprising:
[0020] Under N2 atmosphere, the core-shell powder and the carbonized support were heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300 min, and then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30 min, fully ground and sieved to obtain soft and hard carbon composite negative electrode active materials for sodium ion batteries.
[0021] Preferably, the carbonized support is a zirconium bead with a particle size of 0.05 to 50 mm;
[0022] The mass ratio of the total mass of the carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent to the carbonized support is (10-30):(90-70).
[0023] The present invention provides a sodium ion battery soft and hard carbon composite negative electrode, the composite negative electrode comprising the sodium ion battery soft and hard carbon composite negative electrode active material, a binder and a conductive filler as described in the above technical solution;
[0024] The mass ratio of active material, binder and conductive filler is (6~10):(2~3):(1~2).
[0025] The present invention provides a sodium ion battery, comprising the sodium ion battery soft and hard carbon composite negative electrode described in the above technical solution.
[0026] The present invention provides a sodium ion battery soft and hard carbon composite negative electrode active material, and the preparation raw materials include asphaltene, carbonized reed straw, pore former and sodium supplementer in a mass ratio of (30-50): (15-30): (10-20): (10-25). The present invention adopts carbonized reed straw as hard carbon, which is wrapped by asphaltene soft carbon to form a core-shell structure. In the presence of the pore former and the sodium supplementer, the negative electrode active material has a higher specific surface area and more active sites. The assembled battery has the advantages of large specific capacity and low first cycle loss rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Raman images of active substances of carbonized reed straw powder and soft and hard carbon composite negative electrode powder prepared in Example 2 of the present invention;
[0028] Figure 2 This is a scanning electron microscope (SEM) image of the carbonized reed straw powder prepared in Example 2 of the present invention;
[0029] Figure 3 This is a scanning electron microscope SEM image of the active material powder of the soft and hard carbon composite negative electrode powder of Example 5 of the present invention;
[0030] Figure 4 This is a transmission electron microscope TEM image of the active material powder of the soft and hard carbon composite negative electrode powder of Example 5 of the present invention;
[0031] Figure 5 The first charge and discharge cycle performance diagram of Example 5 of the present invention;
[0032] Figure 6 The first charge and discharge cycle performance diagram of comparative example 2 of the present invention. DETAILED DESCRIPTION
[0033] The present invention provides a sodium ion battery soft and hard carbon composite negative electrode active material. The preparation raw materials include asphaltene, carbonized reed straw, a pore former and a sodium supplementer in a mass ratio of (30-50): (15-30): (10-20): (10-25).
[0034] The present invention uses carbonized reed straw and asphaltene as hard carbon and soft carbon of the negative electrode active material to form a core-shell structure powder, and uses carbonized reed straw as the capsule core, which has the characteristics of low working voltage, high specific capacity, high first-cycle coulomb efficiency, high compaction density, high electronic and ionic conductivity, stable structure (small volume deformation) and air stability, low cost, safety and non-toxicity; the capsule wall uses asphalt-based hard carbon, the negative electrode has good electrochemical properties and high specific capacity, and also has excellent cycle resistance and mechanical strength, which is conducive to promoting environmental sustainable development. In the presence of a pore-forming agent and a sodium supplement, the negative electrode active material has a higher specific surface area and more active sites, and the assembled battery has the advantages of large specific capacity and low first-cycle loss rate.
[0035] The raw materials for preparing the soft and hard carbon composite negative electrode active material of the sodium ion battery provided by the present invention include asphaltene, and the asphaltene is selected from ordinary asphalt powder and high softening point asphalt.
[0036] The raw material for preparing the soft and hard carbon composite negative electrode active material of the sodium ion battery provided by the present invention includes carbonized reed straw; the reed straw contains a large amount of carbon, nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, hydrogen and other nutrient elements, and is rich in organic substances such as cellulose, hemicellulose, lignin and protein. The present invention first carbonizes the reed straw, removes a large amount of water and nitrogen, phosphorus, sulfur, hydrogen and other elements in the reed straw, and makes the loose straw into a dense carbon material.
[0037] The carbonized reed straw of the present invention is prepared according to the following method:
[0038] In a N2 atmosphere, the reed straw was heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300 min, then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30 min, and cooled to obtain carbonized straw.
[0039] In a specific embodiment of the present invention, under N2 atmosphere, the temperature is increased to 450°C at 10°C / min and kept warm for 100 min; then the temperature is continued to be increased to 1300°C at 10°C / min and kept warm for 30 min, cooled to room temperature, fully ground, and passed through a 400-mesh sieve to obtain carbonized reed straw.
[0040] The present invention carbonizes reed straw to obtain carbonized straw, uses hard carbon as active material, mixes it with asphaltene, uses the carbonized straw as a capsule core, and uses the asphaltene as a capsule wall to form a core-shell structure. The composite carbon with this structure has the advantages of a larger specific surface area, more active sites, and a larger specific capacity of an assembled battery, a smaller first-cycle loss rate, and the like.
[0041] The raw materials for preparing the soft and hard carbon composite negative electrode active material of the sodium ion battery provided by the present invention include a pore former and a sodium supplementer; the pore former is selected from melamine. The sodium supplementer is preferably sodium hydrogen phthalate. The present invention adopts the above-mentioned type of pore former, and in the high temperature range, melamine is decomposed into nitrogen, hydrogen and other gases during carbonization to play a pore-forming role, thereby increasing the specific surface area of the powder and providing more active sites. The present invention adopts sodium hydrogen phthalate as a sodium supplementer, and its products of carbon monoxide, carbon dioxide and sodium oxide at high temperature bury sodium in the air on the hard carbon surface in advance, which can improve the problems of excessive loss of specific capacity in the first cycle of the battery and low capacity retention rate after cycling.
[0042] In a specific embodiment of the present invention, the sodium ion battery soft and hard carbon composite negative electrode active material is prepared by raw materials including asphaltene, carbonized reed straw, pore former and sodium supplementer in a mass ratio of 30:30:20:20;
[0043] or comprising asphaltene, carbonized reed straw, pore former and sodium supplement in a mass ratio of 50:15:20:15;
[0044] or comprising asphaltene, carbonized reed straw, pore former and sodium supplement in a mass ratio of 45:15:15:25;
[0045] or comprising asphaltene, carbonized reed straw, pore former and sodium supplement in a mass ratio of 50:30:10:10;
[0046] or comprising asphaltene, carbonized reed straw, pore former and sodium supplement in a mass ratio of 40:20:20:20;
[0047] The present invention provides a method for preparing the soft and hard carbon composite negative electrode active material for a sodium ion battery according to the above technical solution, comprising the following steps:
[0048] The carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent are mixed, solvent toluene is added, stirred evenly, and freeze-dried to obtain core-shell powder;
[0049] The core-shell powder and the carbonized support are carbonized under an inert atmosphere to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery.
[0050] The present invention mixes carbonized reed straw, asphaltene, a pore-forming agent and a sodium supplement, adds solvent toluene, stirs evenly, and freeze-dries to obtain a core-shell powder. The asphaltene wraps the carbonized reed straw to form a core-shell structure. The present invention adopts a freeze-drying process, and in a highly vacuum environment, the carbonized straw is used as a composite material of the capsule core and the asphaltene is used as a capsule wall, and is directly frozen by rapidly evacuating the vacuum chamber in a drying chamber, and the solvent is directly sublimated into a gaseous state without being removed in a liquid state in a condenser. The physical structure and molecular structure of the core-shell powder change very little, and its organizational structure and appearance are well preserved. The freeze-drying temperature in the present invention is -38~-42°C, the vacuum degree is -0.1MPa, and the time is 10~24h.
[0051] The core-shell powder and the carbonized support in the present invention are carbonized under an inert atmosphere, comprising:
[0052] Under N2 atmosphere, the core-shell powder and the carbonized support were heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300 min, and then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30 min, fully ground and sieved to obtain soft and hard carbon composite negative electrode active materials for sodium ion batteries.
[0053] The carbonized support used in the present invention is zirconium beads with a particle size of 0.05-50 mm; the mass ratio of the total mass of the carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent to the carbonized support is (10-30):(90-70).
[0054] In a specific embodiment of the present invention, the temperature is increased to 450°C at a heating rate of 10°C / min, kept warm for 100 minutes, and then continued to be heated to 1200°C at a heating rate of 10°C / min, kept warm for 30 minutes, and cooled to room temperature to obtain a hard carbon negative electrode active material block; it is fully ground and passed through a 400-mesh sieve to obtain a sodium ion battery soft and hard carbon composite negative electrode active material powder.
[0055] The present invention provides a sodium ion battery soft and hard carbon composite negative electrode, the composite negative electrode comprising the sodium ion battery soft and hard carbon composite negative electrode active material, a binder and a conductive filler as described in the above technical solution;
[0056] The mass ratio of active material, binder and conductive filler is (6~10):(2~3):(1~2).
[0057] In a specific embodiment, the mass ratio of the active material, the binder and the conductive filler is 7:2:1.
[0058] The present invention provides a sodium ion battery, comprising the sodium ion battery soft and hard carbon composite negative electrode described in the above technical solution.
[0059] The sodium ion battery provided by the present invention adopts the above-mentioned sodium ion battery soft and hard carbon composite negative electrode, and the negative electrode includes the negative electrode active material described in the above-mentioned technical solution, so that the battery has a higher first cycle coulomb efficiency, a higher first discharge specific capacity; and excellent cycle efficiency.
[0060] In order to further illustrate the present invention, a sodium ion battery soft and hard carbon negative electrode active material and its preparation method and application provided by the present invention are described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention. Example 1
[0061] Take an appropriate amount of reed straw by weight, heat it to 450℃ at 10℃ / min in N2 atmosphere, keep it warm for 100min, then continue to heat it to 1300℃ at 10℃ / min, keep it warm for 30min, and cool it to room temperature. Grind it thoroughly and pass it through a 400-mesh sieve to obtain carbonized reed straw.
[0062] 30 parts of carbonized reed straw, 30 parts of asphaltene, 20 parts of pore-forming agent and 20 parts of sodium supplement were fully mixed and stirred evenly, and 100 parts of solvent toluene were added, stirred evenly, and freeze-dried to obtain core-shell powder; the freeze-drying process was set at a temperature of -40°C, a vacuum degree of -0.1Mpa, and the process was set for 24 hours;
[0063] Under N2 atmosphere, the core-shell powder and the carbonized support (zirconium beads with a particle size of 0.1-2 mm) in a mass ratio of 1:4 were heated to 450°C at a heating rate of 10°C / min, kept warm for 100 min, and then continued to be heated to 1200°C at a heating rate of 10°C / min, kept warm for 30 min, and cooled to room temperature to obtain a hard carbon negative electrode active material block; it was fully ground and passed through a 400-mesh sieve to obtain a sodium ion battery soft and hard carbon composite negative electrode active material powder, with a tested ash content of 0.04%, a moisture content of 0.02%, and a tap density of 0.79.
[0064] The negative electrode active material glass powder, binder (polyvinylidene fluoride), and conductive carbon black (particle size distribution 1~10 μm) powders with a mass ratio of 7:2:1 were mixed, and then an appropriate amount of solvent N-methylpyrrolidone (accounting for 20wt% of the powder) was dropped into the ball mill, and the resulting slurry was coated on copper foil and dried. After vacuum drying at 60°C for 12 hours, it was cut into discs with a diameter of 12 mm and used as negative electrodes. The loading of active material on each pole piece is about 1.8mg / m 2 . The sodium sheet was used as the reference electrode, and the weighed electrode, CR2032 battery shell, diaphragm (glass fiber, Whatman) and nickel foam were placed in an argon-filled glove box. The battery was assembled using a 1 mol / L NaPF6 electrolyte, and the solvents were ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1). CR2032 button cells were prepared in an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). The battery cycle performance was tested using the LAND CT3001A battery test system.
[0065] Embodiment 2~5
[0066] According to the preparation process of Example 1 and the raw material amounts in Table 1, a sodium ion battery soft and hard carbon composite negative electrode active material powder was prepared.
[0067] Table 1
[0068]
[0069] Comparative Example 1
[0070] 0.05 g of Ketjen black was finely ground; 1 g of coal tar pitch was finely ground and dissolved in 30 mL of dichloromethane, and evenly dispersed and mixed with the finely ground Ketjen black, and the dichloromethane was dried to remove the dichloromethane to obtain a mixture of asphalt and Ketjen black; under an argon atmosphere, the mixture of asphalt and Ketjen black was placed in a tube furnace and heated, and the temperature was raised to 200°C at 5°C / min, and stayed for 2 h; then the temperature was raised to 1400°C at 5°C / min, and stayed for 2 h; after cooling to room temperature, it was finely ground to obtain an asphalt-based hard carbon sodium ion battery negative electrode material. 0.45 g of the asphalt-based hard carbon prepared above and 0.05 g of the binder slurry were weighed and evenly coated on the copper foil, and the punch was taken out after vacuum drying at 80°C for 12 h. In a glove box protected by high-purity argon, the prepared electrode and metal sodium sheet were used as the counter electrode, glass fiber diaphragm, and the electrolyte solvent was NaPF6 ester electrolyte, without any other additives, to assemble a 2032 button cell. The electrochemical sodium storage performance test was carried out at room temperature with a voltage range of 0-3 V. The sample was charged at a current density of 0.02 Ag -1 The charge and discharge test was carried out under the conditions, and the specific capacity reached 205mAh g -1 .
[0071] Comparative Example 2
[0072] Add 1.5g of asphalt and 1.5g of calcium gluconate into a mortar and grind manually for 30 minutes to evenly mix the two to obtain a raw carbon source; place the raw carbon source in a high-temperature furnace, heat it to 450°C at a rate of 5°C / min under an argon atmosphere and keep it warm for 1 hour. The resulting product is pickled with a 1 mol / L hydrochloric acid solution, and then centrifuged and washed until the filtered water is pH neutral, then dried and ground into fine powder to obtain a precursor; place the precursor in a high-temperature furnace, heat it to 1200°C at a rate of 10°C / min under an argon atmosphere and keep it warm for 2 hours, cool it, and grind it into fine powder to obtain a sodium ion battery modified asphalt-based hard carbon material. Modified asphalt-based hard carbon material was used as the negative electrode material. To ensure sufficient sodium ions, the half-cell used a sodium metal disc as the counter electrode. The electrolyte used was a dimethyl ether (DME) solution with a concentration of 1 mol / L NaPF6. The electrolyte dosage was 160 μL. The loading amount of the active material on the negative electrode was controlled to be 2 mg cm -2 The assembled battery is 1Ag -1 Under the current density, the initial cycle specific capacity is 173mAh / g and the first cycle coulombic efficiency is 71%.
[0073] Comparative Example 3
[0074] Take an appropriate amount of coconut shell by weight, heat it to 450℃ in N2 atmosphere at 10℃ / min, keep it warm for 100min; then continue to heat it to 1300℃ at 10℃ / min, keep it warm for 30min, and cool it to room temperature. Grind it thoroughly and pass it through a 400-mesh sieve to obtain carbonized coconut shell powder.
[0075] 30 parts of carbonized coconut shell powder, 30 parts of asphaltene, 20 parts of pore-forming agent and 20 parts of sodium supplement agent were fully mixed and stirred evenly, and 100 parts of solvent toluene were added, stirred evenly, and freeze-dried to obtain core-shell powder; after freeze-drying, core-shell powder was obtained; the freeze-drying process was set to a temperature of -40°C, a vacuum degree of -0.1Mpa, and a process of 24 hours;
[0076] In N2 atmosphere, the core-shell powder and the carbonized support were heated to 450℃ at a heating rate of 10℃ / min, kept warm for 100min, and then continued to heat to 1200℃ at a heating rate of 10℃ / min, kept warm for 30min, and cooled to room temperature to obtain a hard carbon negative electrode active material block; fully ground and passed through a 400-mesh sieve to obtain a sodium ion battery soft and hard carbon composite negative electrode active material powder, with an ash content of 0.03%, a moisture content of 0.03%, and a tap density of 0.78.
[0077] The negative electrode active material glass powder, binder (polyvinylidene fluoride), and conductive carbon black (particle size distribution 1~10 μm) powders with a mass ratio of 7:2:1 were mixed, and then an appropriate amount of solvent N-methylpyrrolidone (accounting for 20wt% of the powder) was dropped into the ball mill, and the resulting slurry was coated on copper foil and dried. After vacuum drying at 60°C for 12 hours, it was cut into discs with a diameter of 12 mm and used as negative electrodes. The active material loading on each pole piece is about 1.8g / m 2 . The sodium sheet was used as the reference electrode, and the weighed electrode, CR2032 battery shell, diaphragm (glass fiber, Whatman) and nickel foam were placed in an argon-filled glove box. The battery was assembled using a 1 mol / L NaPF6 electrolyte, and the solvents were ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1). CR2032 button cells were prepared in an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). The battery cycle performance was tested using the LAND CT3001A battery test system.
[0078] Comparative Example 4
[0079] Take an appropriate amount of reed straw by weight, heat it to 450℃ at 10℃ / min in N2 atmosphere, keep it warm for 100min, then continue to heat it to 1300℃ at 10℃ / min, keep it warm for 30min, and cool it to room temperature. Grind it thoroughly and pass it through a 400-mesh sieve to obtain carbonized reed straw.
[0080] 30 parts of carbonized reed straw, 30 parts of asphaltene, 20 parts of pore-forming agent and 20 parts of sodium supplement agent were fully mixed and stirred evenly, and 100 parts of solvent toluene were added, stirred evenly, and freeze-dried to obtain core-shell powder;
[0081] In N2 atmosphere, the core-shell powder and the carbonized support were heated to 450℃ at a heating rate of 10℃ / min, kept warm for 100min, and then continued to heat to 1200℃ at a heating rate of 10℃ / min, kept warm for 30min, and cooled to room temperature to obtain a hard carbon negative electrode active material block; after fully grinding and passing through a 400-mesh sieve, a sodium ion battery soft and hard carbon composite negative electrode active material powder was obtained, with an ash content of 0.04%, a moisture content of 0.03%, and a tap density of 0.82.
[0082] The negative electrode active material glass powder, binder (polyvinylidene fluoride), and conductive carbon black (particle size distribution 1~10 μm) powders with a mass ratio of 7:2:1 were mixed, and then an appropriate amount of solvent N-methylpyrrolidone (accounting for 20wt% of the powder) was dropped into the ball mill, and the resulting slurry was coated on copper foil and dried. After vacuum drying at 60°C for 12 hours, it was cut into discs with a diameter of 12 mm and used as negative electrodes. The active material loading on each pole piece is about 1.8g / m 2 . The sodium sheet was used as the reference electrode, and the weighed electrode, CR2032 battery shell, diaphragm (glass fiber, Whatman) and nickel foam were placed in an argon-filled glove box. The battery was assembled using a 1 mol / L NaPF6 electrolyte, and the solvents were ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1). CR2032 button cells were prepared in an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). The battery cycle performance was tested using the LAND CT3001A battery test system.
[0083] Comparative Example 5
[0084] In parts by weight, 30 parts of reed straw, 30 parts of asphaltene, 20 parts of pore-forming agent and 20 parts of sodium supplement agent are fully mixed and stirred evenly, and 100 parts of solvent toluene are continuously added, stirred evenly, and freeze-dried to obtain core-shell powder; after freeze-drying, core-shell powder is obtained; the freeze-drying process is set at a temperature of -40°C, a vacuum degree of -0.1Mpa, and the process is set for 24 hours;
[0085] Under N2 atmosphere, the core-shell powder and the carbonized support were heated to 450°C at a heating rate of 10°C / min, kept warm for 100 min, and then continued to be heated to 1200°C at a heating rate of 10°C / min, kept warm for 30 min, and cooled to room temperature to obtain a hard carbon negative electrode active material block; it was fully ground and passed through a 400-mesh sieve to obtain a sodium ion battery soft and hard carbon composite negative electrode active material powder, with a tested ash content of 0.03%, a moisture content of 0.04%, and a tap density of 0.77.
[0086] The negative electrode active material glass powder, binder (polyvinylidene fluoride), and conductive carbon black (particle size distribution 1~10 μm) powders with a mass ratio of 7:2:1 were mixed, and then an appropriate amount of solvent N-methylpyrrolidone (accounting for 20wt% of the powder) was dropped into the ball mill, and the resulting slurry was coated on copper foil and dried. After vacuum drying at 60°C for 12 hours, it was cut into discs with a diameter of 12 mm and used as negative electrodes. The active material loading on each pole piece is about 1.8g / m 2 . The sodium sheet was used as the reference electrode, and the weighed electrode, CR2032 battery shell, diaphragm (glass fiber, Whatman) and nickel foam were placed in an argon-filled glove box. The NaPF6 electrolyte with a concentration of 1 mol / L was used in the battery assembly process, and its solvent was ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1). CR2032 button batteries were prepared in an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). The battery cycle performance was tested using the LAND CT3001A battery test system.
[0087] The present invention tests the performance of sodium ion batteries assembled with negative electrode materials prepared in the examples and comparative examples. At a current density of 0.1 A / g, the results are shown in Tables 2 and 3:
[0088] Table 2
[0089]
[0090] Table 3
[0091]
[0092] As can be seen from the above embodiments, the present invention provides a sodium ion battery soft and hard carbon composite negative electrode active material, and the raw materials for preparation include asphaltene, carbonized reed straw, pore-forming agent and sodium supplement agent in a mass ratio of (30-50): (15-30): (10-20): (10-25). The present invention adopts carbonized reed straw as hard carbon, which is wrapped by asphaltene soft carbon to form a core-shell structure. In the presence of pore-forming agent and sodium supplement agent, the negative electrode active material has a higher specific surface area and more active sites. The assembled battery has the advantages of large specific capacity and small first cycle loss rate. The experimental results show that the soft and hard carbon composite negative electrode powder is used in sodium ion batteries, and the first reversible capacity is above 307.1-330.1 mAh / g at a current density of 0.1 A / g, and the first coulombic efficiency is ≥89.2%; the battery has a discharge capacity of 238.0-275.3 mAh / g after 1000 cycles, and a cycle efficiency of ≥76.5%.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A sodium ion battery soft and hard carbon composite negative electrode active material, the preparation raw materials include asphaltene, carbonized reed straw, pore-forming agent and sodium supplement agent in a mass ratio of (30-50): (15-30): (10-20): (10-25); The carbonized reed straw is prepared according to the following method: In a nitrogen atmosphere, the reed straw is heated to 440-460°C at a heating rate of 9-11°C / min, kept at this temperature for 10-300 minutes, then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept at this temperature for 10-30 minutes, and cooled to obtain carbonized reed straw; The pore-forming agent is melamine; the sodium supplement is sodium hydrogen phthalate; The method for preparing the soft and hard carbon composite negative electrode active material for a sodium ion battery comprises the following steps: The carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent are mixed, solvent toluene is added, stirred evenly, and freeze-dried to obtain core-shell powder; Carbonizing the core-shell powder and the carbonized support under an inert atmosphere to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery; The freeze-drying temperature is -38 to -42°C, the vacuum degree is -0.1MPa, and the time is 10 to 24h; The core-shell powder and the carbonized support are carbonized under an inert atmosphere, comprising: In a N2 atmosphere, the core-shell powder and the carbonized support are heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300min, and then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30min, fully ground, and sieved to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery; The carbonized support is a zirconium bead with a particle size of 0.05 to 50 mm; The mass ratio of the total mass of the carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent to the carbonized support is (10-30):(90-70).
2. A method for preparing the soft and hard carbon composite negative electrode active material for sodium ion batteries according to claim 1, comprising the following steps: The carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent are mixed, solvent toluene is added, stirred evenly, and freeze-dried to obtain core-shell powder; Carbonizing the core-shell powder and the carbonized support under an inert atmosphere to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery; The freeze-drying temperature is -38 to -42°C, the vacuum degree is -0.1MPa, and the time is 10 to 24h; The core-shell powder and the carbonized support are carbonized under an inert atmosphere, comprising: In a N2 atmosphere, the core-shell powder and the carbonized support are heated to 440-460°C at a heating rate of 9-11°C / min, kept warm for 10-300min, and then continued to be heated to 1000-1500°C at a heating rate of 9-11°C / min, kept warm for 10-30min, fully ground, and sieved to obtain a soft and hard carbon composite negative electrode active material for a sodium ion battery; The carbonized support is a zirconium bead with a particle size of 0.05 to 50 mm; The mass ratio of the total mass of the carbonized reed straw, asphaltene, pore-forming agent and sodium supplement agent to the carbonized support is (10-30):(90-70).
3. A soft and hard carbon composite negative electrode for a sodium ion battery, characterized in that: The composite negative electrode comprises the sodium ion battery soft and hard carbon composite negative electrode active material according to claim 1, a binder and a conductive filler; The mass ratio of active material, binder and conductive filler is (6-10):(2-3):(1-2).
4. A sodium ion battery, comprising the sodium ion battery soft and hard carbon composite negative electrode according to claim 3.
Citation Information
Patent Citations
Asphalt-based soft carbon composite cellulose hard carbon negative electrode material and preparation method thereof
CN115744872A
Soft and hard carbon composite material for sodium ion battery as well as preparation method and application of soft and hard carbon composite material
CN116454227A
Preparation method and preparation device of hard carbon negative electrode material
CN116789102A
Asphalt-based hard carbon composite material for sodium ion battery and preparation method of asphalt-based hard carbon composite material
CN117819523A